Morale, training, commitment and safety of Malaysian Army infantry officers during flood disaster response missions - Cheong, Rayyan Tian Ming; Roslan, Nur Hidayah; Abdullah, Haslinda; Mohamed, Rosmah (Academic Research Publishing, 2019)
An effective disaster response is crucial to any organizations. When a disaster happens, the response must be fast, coordinated and appropriate so that it will minimize the human and economic cost of disaster. In Malaysia, several states of the Peninsular are frequently affected by flooding during the monsoon season. The military has played a crucial role in disaster management and relief. The Malaysian Army are well trained in terms of combat. However, little is known about their effectiveness in handling disaster operations. The objective of this research is to examine Malaysian Army Infantry Officers’ morale, training, safety and commitment to disaster responses in the context of flood disasters in Malaysia. This research found that training, commitment, morale and safety are the critical factors that influence effective disaster responses in the Malaysian Army. This study’s methodology is descriptive and exploratory, using qualitative methods. Data collection was carried out through conducting interviews and focus groups with Malaysian Army Infantry Officers located in the Central region, Northern region, Southern region and East Coast who have been involved in flood disaster operations for the past three years. Data collected were transcribed, categorized and grouped into themes. This research found that even without specific training in disaster relief, the Malaysian Army Infantry officers are inspired, positive and ever ready to take up the responsibilities given, and that they execute them wholehearted during disaster responses. In addition, in terms of safety, the Malaysian Army has safety guidelines and protocols to protect its soldiers during disaster missions.